Efektivitas Penggunaan Pendapatan Desa Dalam Menunjang Pembangunan Di Kampung Kadun Jaya - Zuljhijrah Zuljhijrah; Abu Bakar (STIE Jambatan Bulan, 2023)
This study aims to determine the effectiveness of using village income in supporting development in Kampung Kadun Jaya. The research method used in this research is descriptive research method. The data used are qualitative and quantitative data, which were collected using observation, interviews, documentation and questionnaires. To measure the effectiveness of using village income in supporting development in Kampung Kadun Jaya, the concept of respondent analysis was used, with development according to the objectives of this study. The results of this study indicate that the use of village income to support development in Kampung Kadun Jaya has been running effectively